PRELIMINARY RESULTS ON THE APPLICATION OF SENTINEL-1 SAR IMAGING FOR SHORELINE DETECTION - Mulyadi, Budi
This study discusses the shoreline extraction in the western Java area on the northern coast and the quality assessment of the shoreline made by using SAR (Synthetic-Aperture Radar) image data. Study is carried out by separating land and sea objects based on the DN (Digital Number) value on the SAR image and drawing a line between the two objects. To improve the reliability of the classification of sea and land objects, random error removal in the image is done by averaging the DN values on the available images. The optimum number of images that need to be used is searched for with the criteria 95% random errors have been lost. The comparison of random error elimination is done between image from averaging method to image using Lee filter. To assess the quality of the shoreline produced, a comparison is made of the produced shoreline to the shoreline issued by BIG (Geospatial Information Agency) with a scale of 1: 25000. This is done by calculating the samples distance between the shoreline produced by the shoreline of BIG every interval of 25 m and averaging these samples. From this method, shoreline extraction is successfully carried out and it was found that 18 data were found to be sufficient to meet the criteria mentioned. Comparison with Lee Filter uses a window size of 3x3 pixels, 5x5 pixels, and 7x7 pixels found that this method managed to reduce random errors by 53%, 63%, 67% respectively. The comparison of the distance between the two shorelines obtained is 148 m. The results of this research are expected to assist in the provision of information on coastal areas, especially shorelines in the study area.